Pengaruh Loneliness terhadap Self Esteem pada Pengguna Aplikasi Bumble - Febriani Purnama Dewi; Muhammad Ilmi Hatta (UNISBA Press, 2024)
Abstract. Self esteem refers to an individual's evaluation of themselves, encompassing both positive and negative attitudes, and has a significant impact on psychological well being. Loneliness is a mental condition characterized by feelings of emptiness and isolation. Previous research has shown a negative relationship between loneliness and self esteem, indicating that individuals experiencing loneliness often suffer from a decrease in self-esteem. In the modern social era, the use of dating applications has become increasingly popular among the younger generation, including the